Media ownership and coverage patterns of established, disruptive, and unconventional climate advocacy groups - Robyn E. Gulliver; Xiongzhi Wang; Winnifred R. Louis; Kelly S. Fielding; Rebecca M. Colvin (Climatic Change, 2025)
Groups advocating on climate and environmental issues often seek to obtain media coverage to increase public awareness of their cause, yet comparatively little is understood about the factors influencing the volume and content of that coverage. This study investigates the quantity and characteristics of media coverage of climate advocacy groups through a mixed-method analysis of 17,380 Australian media articles published between 2017–2022. Four types of advocacy groups were the focus: ‘Established’ groups (large professionalised environmental groups); ‘Disruptive’ groups (the greatest use of civil resistance tactics); and two types of what we call ‘Unconventional advocates’ – those who advocate for action on climate change but from a social identity position that is either typically not associated with climate action (‘Role-based unconventional advocates’, such as parents or doctors) or has a history of conflict with climate or other environmental causes and environmentalists (‘Conflict-spanning unconventional advocates’, such as farmers and political conservatives). Findings indicate that linguistic cues associated with conflict, achievement, and emotional sentiment differed significantly according to the advocacy group type and media ownership. While Established groups gained the greatest volume of coverage, Disruptive groups attracted the highest conflict language and lowest achievement language, particularly in outlets published by News Corp (the Murdoch owned media company). Meanwhile, conflict-spanning unconventional advocates received coverage using language with the lowest levels of conflict and highest levels of achievement. Our findings highlight the potential for new types of climate advocates to gain comparative sympathetic media coverage and potentially expand the social basis of support for climate action.

Key attributes for effective knowledge brokering at the interface of environmental science and management - Denis B. Karcher; Christopher Cvitanovic; R. M. Colvin; Ingrid van Putten; Ramona Dalla Pozza; Stephen Posner (Sustainability Science, 2025)
Spanning the boundaries between research and decision-making is critical for supporting environmental management. One way to do so is through knowledge brokers who, among other things, work to build social networks among decision-makers and researchers, facilitating their interaction and exchange of knowledge. While knowledge brokering has received increasing attention in the literature, critical gaps in our knowledge limit their effective recruitment and implementation, which demands for a better understanding of the personal attributes needed for their success. Such an understanding is also necessary to support the evaluation of knowledge brokering activities. Therefore, in this study, we investigate the question ‘what are the most important attributes for being a knowledge broker at the interface of environmental research and management’, and how is knowledge brokering evaluated. We do so through the study of Australia’s National Environmental Science Program (NESP) which employs a range of professional knowledge brokers, 14 of whom participated in this study. Specifically, we performed a quantitative ranking exercise (Q-methodology) and an online survey. Results show that the most important attributes to knowledge brokering were interpersonal social competencies of a unifying nature. As such, Being good at seeing opportunities for collaboration, Being able to tailor communication to different audiences, and Being able to ask questions were the most highly ranked attributes. In the dimension of evaluation, survey results show that NESP knowledge brokers are mainly evaluated through metrics relating to immediate delivery and engagement (mostly quantitative measures) and medium-term impact on end-users (qualitative measures). However, participants envisioned better options to capture the impact/value of knowledge brokering by evaluating long-term impacts and efforts throughout the full brokering process to better capture value addition in line with their goals, strategies, and required attributes. The new knowledge generated through our findings offers an applied contribution to the practice of knowledge brokering, suggesting that knowledge brokering is a distinct and complex career whereby different knowledge brokers with complementary skill sets appear relevant to perform all tasks along a knowledge brokering timeline. As such, our results also emphasize the need for bespoke approaches to evaluation that are tailored towards the diverse goals, strategies, and personal contributions of knowledge brokers to support their career progression and maximise outcomes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Boundary spanning at the science–policy interface: the practitioners’ perspectives - A. T. Bednarek; C. Wyborn; C. Cvitanovic; R. Meyer; R. M. Colvin; P. F. E. Addison; S. L. Close; K. Curran; M. Farooque; E. Goldman; D. Hart; H. Mannix; et al. (Sustainability Science, 2018)

Nickel and Copper Toxicity to Embryos of the Long-Spined Sea Urchin, Diadema savignyi - G. Rosen; I. Rivera-Duarte; M. A. Colvin; R. E. Dolecal; L. J. Raymundo; P. J. Earley (Bulletin of Environmental Contamination and Toxicology, 2015)

The Pel and Psl polysaccharides provide Pseudomonas aeruginosa structural redundancy within the biofilm matrix - Kelly M. Colvin; Yasuhiko Irie; Catherine S. Tart; Rodolfo Urbano; John C. Whitney; Cynthia Ryder; P. Lynne Howell; Daniel J. Wozniak; Matthew R. Parsek (Environmental Microbiology, 2012)
Summary Extracellular polysaccharides comprise a major component of the biofilm matrix. Many species that are adept at biofilm formation have the capacity to produce multiple types of polysaccharides. Pseudomonas aeruginosa produces at least three extracellular polysaccharides, alginate, Pel and Psl, that have been implicated in biofilm development. Non‐mucoid strains can use either Pel or Psl as the primary matrix structural polysaccharide. In this study, we evaluated a range of clinical and environmental P. aeruginosa isolates for their dependence on Pel and Psl for biofilm development. Mutational analysis demonstrates that Psl plays an important role in surface attachment for most isolates. However, there was significant strain‐to‐strain variability in the contribution of Pel and Psl to mature biofilm structure. This analysis led us to propose four classes of strains based upon their Pel and Psl functional and expression profiles. Our data also suggest that Pel and Psl can serve redundant functions as structural scaffolds in mature biofilms. We propose that redundancy could help preserve the capacity to produce a biofilm when exopolysaccharide genes are subjected to mutation. To test this, we used PAO1, a common lab strain that primarily utilizes Psl in the matrix. As expected, a psl mutant strain initially produced a poor biofilm. After extended cultivation, we demonstrate that this strain acquired mutations that upregulated expression of the Pel polysaccharide, demonstrating the utility of having a redundant scaffold exopolysaccharide. Collectively, our studies revealed both unique and redundant roles for two distinct biofilm exopolysaccharides.

PCR-based detection and partial genome sequencing indicate high genetic diversity in Bangladeshi begomoviruses and their whitefly vector, Bemisia tabaci - M. N. Maruthi; A. R. Rekha; S. H. Mirza; S. N. Alam; J. Colvin (Virus Genes, 2007)

Mating Frequency, Fecundity and Fertilization Success in the Hide Beetle, Dermestes Maculatus - Therésa M. Jones; Kathryn B. McNamara; Paul G. R. Colvin; Rebecca Featherston; Mark A. Elgar (Journal of Insect Behavior, 2006)

East African cassava mosaic Zanzibar virus – a recombinant begomovirus species with a mild phenotype - M. N. Maruthi; S. Seal; J. Colvin; R. W. Briddon; S. E. Bull (Archives of Virology, 2004)